Controls of faulting on synrift infill patterns in the Eocene PY4 Sag, Pearl River Mouth Basin, South China Sea. Issue 1 (2nd January 2019) - Ge, J.; Zhu, X.; Yu, F.; Jones, B. G.; Tao, W.
Abstract: Tectono-stratigraphic analysis of the Eocene PY4 Sag, Pearl River Mouth Basin, reveals that the evolution of normal faulting exerted an important control on the basin infill patterns. Seismic, well log and core data jointly indicate the Eocene Wenchang Formation can be subdivided into four third-order sequences that are related to early rift (WSQ1), rift climax (WSQ2–3) and late rift (WSQ4) stages. During the early rift stage, the PY4 Sag was defined by three, small-sized depocentres; it was related to low tectonic subsidence and likely overfilled by footwall-derived fan-delta deposits. The isolated depocentres coalesced and formed a larger and more uniform depocentre during the rift climax stage. Significantly increased tectonic subsidence during the rift climax WSQ2 sub-stage gave rise to prominent deep lake deposition including nearshore subaqueous fans, turbidite fan deposits and good source rocks. Two sediment infill patterns adjacent to boundary fault are developed during the rift climax WSQ3 sub-stage: (i) a more likely sediment balance-filled pattern controlled by the low-angled fault and (ii) a sediment under-filled pattern adjacent to the relatively high-angle boundary fault. The late rift stage was characterised by a waned displacement on the NE-striking fault but an increase in displacement on E-striking rift-related faults; this non-synchronous faulting has led to the sediment overfilled pattern observed in the South Sub-sag but a more sediment balance-fill on the South-western Slope. The variability in the basin infill patterns is suggested to have resulted from the different fault displacement patterns, which are closely linked to the boundary fault angles and possible stress field transitions during the basin evolution. This study may provide potential implications for basin infill evaluations in the Eocene Pearl River Mouth Basin and other similar rift systems.